1967
DOI: 10.1001/jama.1967.03130140120028
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Caused by Hypersensitivity to Polymyxin B Sulfate

Abstract: A patient had reversible acute renal failure associated with polymyxin B sulfate therapy. Unusual cells in the urinary sediment, renal glycosuria, and eosinophilia during the oliguric stage were interesting clinical features. A renal biopsy performed early in the course of acute renal failure revealed severe tubular damage as well as an acute diffuse interstitial nephritis. The clinical and histological findings suggested that there were two pathogenetic mechanisms producing the symptoms. One was the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study on the nephrotoxicity of colistin reported patients clinically diagnosed with drug-related acute tubular necrosis, with histological confirmation in three of them (33). Beirne et al also reported acute interstitial nephritis due to hypersensitivity to this antibiotic (31).…”
Section: Discussionmentioning
confidence: 91%
“…A study on the nephrotoxicity of colistin reported patients clinically diagnosed with drug-related acute tubular necrosis, with histological confirmation in three of them (33). Beirne et al also reported acute interstitial nephritis due to hypersensitivity to this antibiotic (31).…”
Section: Discussionmentioning
confidence: 91%